Phase I Clinical Trial of the Mammalian Target of Rapamycin Inhibitor Everolimus in Combination With Oral Topotecan for Recurrent and Advanced Endometrial Cancer. Issue 3 (1st March 2014) - Acevedo-Gadea, Carlos; Santin, Alessandro D.; Higgins, Susan A.; Urva, Shweta; Ratner, Elena; Silasi, Dan-Arin; Azodi, Masoud; Rutherford, Thomas; Schwartz, Peter E.; Abu-Khalaf, Maysa M.
Abstract : Objectives: Preclinical data suggest that mammalian target of rapamycin inhibitors may potentiate the efficacy of topotecan. We evaluated the optimal schedule of oral topotecan in combination with everolimus in patients with endometrial cancer. Methods: Women with a history of advanced or recurrent endometrial cancer were enrolled. Escalating dose of oral topotecan (1.5 mg/m 2, 1.9 mg/m 2, and 2.3 mg/m 2 ) daily on days 1 to 5 and everolimus (5 mg every other day, 5 mg daily, and 10 mg daily) were administered in a 21-day cycle. A "run-in" treatment of topotecan daily for 5 days followed by everolimus for 7 days (4–7 doses depending on dose level) was administered for the purpose of pharmacokinetic assessments. Results: Ten patients were enrolled on the study, and 9 were evaluable for safety analysis. A total of 28 cycles were administered (range, 1–10 cycles per patient). The patients had a median age of 73 years (range, 42–79 years). Previous lines of chemotherapy were 1 (n = 2), 2 (n = 5), 3 (n = 2), and 4 (n = 1). Seven patients had previous vaginal brachytherapy, and 2 had pelvic external beam radiation therapy. The median number of cycles (including cycle 1) is 2 (range, 1–10). Dose-limiting toxicity occurred in 3 patients (1 patient treated with 1.9-mg/m 2 topotecan and 5-mg everolimus given every other day as well as 2 patients treated with 1.9-mg/m 2 topotecan and 5-mg of everolimus daily) and included neutropenia and thrombocytopenia. Seven patients were evaluable for response. Stable disease was the best response in 3 patients who completed the 3, 4, and 10 cycles each. Conclusions: The dose-limiting toxicity for the combination of oral topotecan and everolimus was myelosuppression. The maximum tolerated dose was topotecan 1.9 mg/m 2 on days 1 to 5 in combination with oral everolimus 5 mg every other day. Administration of higher dose of each agent in combination was limited because of overlapping myelosuppression.